EVALUATING PRACTICAL VS. THEORETICAL WATER CONSUMPTION IN MODIFIED AIR COOLERS - Faiz F.M. AL-Makhul,; AL-Badri Samir. B. Salman, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to investigate the impact of increased water flow and two different air speeds on water consumption and cooling performance in modify air coolers. An experiment was conducted using an air cooler with an additional water pump to facilitate increased water flow. One Way ANOVA with regression and Tukey was used. Findings revealed that practical water consumption significantly surpassed theoretical estimates, primarily due to heightened resistance encountered by water as it traversed the cooling pads. Notably, the implementation of two water pumps improved cooling, effectively lowering room temperature by7-10 °C (Δt of 9.4°C); however, this enhancement was accompanied by increased power consumption. Statistical analysis showed significant differences in practical water consumption between different treatment groups (Q1S2-Q1S1,Q1S2-Q2S2,Q1S2-Q2S2,Q2S2-Q1S2, Q2S1-Q1S2)(P